Kinetics Study on Hydrothermal Decomposition of Glucose in NaOH Solution with CuO Catalyst - Bregas Siswahjono Tatag Sembodo; Tatra Prima Baladina; Muhammad Yusuf Haidar (Program studi Teknik Kimia UNS, 2021)
Biomass is an abundant resource of renewable energy and can be processed into various chemicals. In its development, hydrothermal decomposition became a method that was considered quite efficient. This study aimed to determine reaction kinetics and product composition of hydrothermal decomposition process with CuO catalyst. Experiment was conducted by heating 10 grams glucose in 80 mL NaOH solution at temperatures of 33, 50, 110, 210, 260, 280, and 288oC using CuO catalyst. Reaction was conducted in autoclave equipped with a magnetic stirrer. After being heated, autoclave was cooled to ambient temperature. Treated material is filtered to separate insoluble solid and liquid phases. After being separated, solid residue was dried in oven at 105oC for 24 hours. Filtrate composition was analyzed by GC-MS method and glucose concentration was analyzed by Lane Eynon method. Filtrate was atmospherically distilled at 100oC before GC-MS analysis to ensure that sample was free of water and glucose residue. According to kinetics calculation, reaction was 2nd order, activation energy was 28.894 kJ/mol, and pre-exponential factor was 4.17×104 min-1. GC-MS analysis showed that there were 20 compounds contained in product sample with 3 dominant compounds in form of 4,5-Dibromo-hex-2-enoic acid methyl ester, 2-Bromooctadecanal, and 9-Octadecenoic acid, propyl ester.